PENENTUAN SAAT YANG TEPAT BAGI SEBUAH ORGANISASI BISNIS UNTUK BERALIH DARI SPREADSHEET KE APPLICATION-SPECIFIC SOFTWARE (STUDI KASUS ATAS BEBERAPA PERUSAHAAN DI JAWA BARAT) - Christian C. Henry (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
Currently, almost all business organizations use spreadsheet. In some cases, the using of spreadsheet is appropriate, but in other cases, it is not. When the using of spreadsheet is not appropriate anymore, an organization needs to alter from spreadsheet to application-specific software. There are eight factors that should be considered by management in determining whether or not to alter from spreadsheet. These factors are software resources, people resources, data resources, hardware resources, business complexity, network resources, cost of alteration, and company readiness. To determine when the right time to alter is, the eight factors are weighted and an alter or not-to-alter decision is made on each factor. The development of information technology and business environment in general might increase or decrease the factors that are need to be considered by management when they make decision whether or not to alter from spreadsheet to application-specific software.